Smallholder Farmer’s Livelihood Diversification as a Response to Changed Climatic Patterns in Chongwe District, Zambia. - Jacqueline, Mbewe; Mubanga, Kabwe Harnadih (Journal of Agricultural Policy, 2020)
Purpose: Climate change affects local and global rainfall patterns and hence has a counter effect on smallholder agriculture. Impacts of climate change on agriculture are largely due to rainfall variability resulting in reduced yields due to crop-water stress and emergency of pathogens and diseases. In Zambia, climate change has been manifested through increased intensity of droughts and floods. These rainfall anomalies adversely affect agriculture and food systems. In order to survive the impacts of climate change and variability, smallholder farmers in Chongwe have adopted their livelihoods and farming systems to the new climatic patterns. Methodology: This study assessed how smallholder farmers in Chongwe District have adopted their livelihoods as a response to changed climatic conditions. It also investigated the perceptions of smallholder farmers as regards changes in aspects of their climatic conditions. Data collection involved a critical review of literature related to climate change and agriculture, observations, semi- structured interviews with 60 smallholder farmers and eight key informants. The data were analysed using multiple analysis techniques which included the descriptive statistics, One-way analysis of Variance (ANOVA), and the post-hoc Least Square Difference for pairwise comparisons of incomes from different livelihoods engaged in by smallholder farmers .The gendered comparisons of livelihood engagement was done using the chi-square test of association. Findings: The results showed that all farmers perceived occurrence of changes in climatic conditions in the light of changed rainfall patterns in that there has been uncertainty in onset of rains, short rainy season, more intermittent rainfall and increased frequency of intra-seasonal droughts. These changes have led to farmers to adopt such farming techniques as potholing in preference to oxen and tractor ploughing when farming is done on smaller pieces of land. There was a significant difference in the mean annual incomes generated from on-farm livelihoods (ZMW 3677.59; n=58) and off-farm livelihoods (ZMW 6840.91; n = 58) (p= 0.001). Farmers generated the highest income returns by engaging in casual work (ZMW 10307.69; n = 13) compared to every other livelihoods common in the area such as gardening (p=0.002), petty trade (p=0.002) and on-farm livelihoods (p=0.001). Contribution to policy, theory and practice: It was therefore concluded that diversification of income through diversified livelihoods would help smallholder farmers enhance their resilience in the face of changed climatic conditions. On-farm livelihoods should not always be the main income source for farmers as results indicated that farmers engaged in casual work generated higher incomes than those who depended on farming. It was recommended that policy direction should be towards introduction of a gender responsive credit facility that can help improve women's engagement in off-farm income generating livelihoods, as well as encourage climate change resilience.